A change management approach to improving safety and preventing needle stick injuries. Issue 5 (September 2017) - Aziz, Ann-Marie
Key drivers for preventing healthcare-associated infection (HCAI) include evidence-based practices and procedures that prevent infection. Among the current guidance for preventing HCAIs is evidence and mandatory requirements for reducing needle stick injuries (NSIs). This article highlights how John Kotter's model for change could help healthcare workers plan for successful and sustained deployment of needle safety devices (NSDs) and ultimately reduce the risk of a NSI.